2001
DOI: 10.1128/jb.183.8.2576-2585.2001
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Organization of the Region Encoding Regulation, Biosynthesis, and Transport of Rhizobactin 1021, a Siderophore Produced by Sinorhizobium meliloti

Abstract: Eight genes have been identified that function in the regulation, biosynthesis, and transport of rhizobactin 1021, a hydroxamate siderophore produced under iron stress by Sinorhizobium meliloti. The genes were sequenced, and transposon insertion mutants were constructed for phenotypic analysis. Six of the genes, named rhbABCDEF, function in the biosynthesis of the siderophore and were shown to constitute an operon that is repressed under iron-replete conditions. Another gene in the cluster, named rhtA, encodes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
175
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 176 publications
(180 citation statements)
references
References 55 publications
3
175
0
Order By: Relevance
“…The uptake of iron is another crucial aspect of rhizobia metabolism, because enzymes related to nitrogen fixation, such as nitrogenase and leghemoglobin, contain iron as cofactor (Lynch et al 2001;Persmark et al 1993). Ampe et al (2003) found that luteolin significantly induces the expression of three genes involved in iron metabolism in E. meliloti 1021.…”
Section: Discussionmentioning
confidence: 99%
“…The uptake of iron is another crucial aspect of rhizobia metabolism, because enzymes related to nitrogen fixation, such as nitrogenase and leghemoglobin, contain iron as cofactor (Lynch et al 2001;Persmark et al 1993). Ampe et al (2003) found that luteolin significantly induces the expression of three genes involved in iron metabolism in E. meliloti 1021.…”
Section: Discussionmentioning
confidence: 99%
“…This implies that R. palustris uses a large number of different types of siderophores for iron acquisition. However, genes rpa2388-rpa2390 to synthesize only one siderophore, rhizobactin 37 , were detected suggesting that R. palustris may transport iron-loaded siderophores produced by other soil bacteria. As many as seven of the ECF sigma factors encoded by R. palustris are either translationally coupled to ferrisiderophore-like receptor genes or are located very close to genes involved in iron acquisition; in one case siderophore biosynthesis genes and in another, a predicted heme uptake system.…”
Section: Transportmentioning
confidence: 99%
“…The first of these to be discovered were the exochelins and mycobactins of Mycobacter tuberculosis (69), rhizobactin 1021 from a terrestrial, nitrogen-fixing symbiont (70,71), and acinetoferrin (72) from the pathogens Acinetobacter haemoliticus and Acinetobacter baumanii. The amphiphilic marinobactins and acquachelins have been discovered more recently in marine bacteria, (73), indicating that such structures are widely distributed in nature.…”
Section: Iron In Supramolecular Assembliesmentioning
confidence: 99%